Whole Grape Pomace Flour as Nutritive Ingredient for Enriched Durum Wheat Pasta with Bioactive Potential - Carmela Gerardi; Leone D’Amico; Miriana Durante; Maria Tufariello; Giovanna Giovinazzo (Foods, 2023)
In this study, grape pomace is used as an ingredient to fortify pasta. The grape pomace phenolic component is highly accessible and available for metabolization in the human gut. Hence, grape pomace can be exploited as a source of polyphenols and fiber for sustainable and dietary beneficial food production. Analyses of soluble and bound phenols and volatile compounds in raw and cooked pasta were performed. In the uncooked pasta fortified with pomace, the content of soluble and bound phenolic molecules increased significantly. During the cooking process, the bound phenols were lost, while the soluble phenols doubled. The whole grape pomace flour as a pasta ingredient increased the fiber component by at least double, increased the soluble polyphenol component by at least 10 times, and doubled the isoprenoids (toco-chromanols and carotenoids) while maintaining the unaltered fatty acid content after cooking. In accordance with the polyphenol content, antioxidant activity resulted higher than that of the control pasta. Analysis of volatile compounds in fortified pasta, both uncooked and cooked, indicated an improvement in aromatic profile when compared to the control pasta. Our results show that durum wheat pasta fortified with whole pomace flour has bioactive potential for the reuse of food industry byproducts.